APPLICATION OF COMPUTATIONAL METHODS IN DRUG DISCOVERY - P.L.Sujatha; K.Anbu Kumar; P.Devendran; S.P.Preetha; Manikkavasagan Ilangopathy3 (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Rational drug design, is the inventive process of finding new medications based on knowledge of the biological target. Drug design involves the design of small molecules that are complementary in shape and charge to the bimolecular target to which they interact and therefore will bind to it. In the experiment based approach, drugs are discovered through trial and error. With high R&D cost and consumption, computational drug discovery helps scientists gain insight into drug receptor interactions and reduce time and cost. Scientists can predict whether the molecule will succeed or fail in the market. Currently, the process of drug designing increasingly relies on computer modeling techniques. This type of modeling is often referred to as computer-aided drug design. In computational drug discovery, different computational tools, methods, and software are used to simulate drug receptor interactions. Using computational drug discovery helps scientists gain insight into drug receptor interactions with less time and cost.